Evaluasi Instalasi Pengolahan Air Limbah Domestik PT. B - Berlian Aura Aprilia; Teguh Taruna Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
B is a livestock industry company located in Ngadirenggo Village, Wlingi District, Blitar Regency. The main focus of environmental pollution by PT. B leads to water pollution, especially rivers. Domestic Wastewater Treatment Plant (WWTP) PT. B comes from 4 sources, namely Mess, MCC (Milk Collect Center), Canteen, and Laundry Room which are then discharged into the Genjong River water body. This study aims to determine the characteristics of wastewater in the domestic Wastewater Treatment Plant (WWTP) of PT. B, analyze the effectiveness of the performance of domestic WWTP in treating waste, and evaluate domestic WWTP buildings when compared to the design criteria of water treatment plants in the literature study. The research was carried out for approximately 3 months starting from January 20, 2025 to April 14, 2025. The location of the research of PT. B. Primary and secondary data collection was carried out in this study. The quality of the wastewater produced exceeds the quality standards set by the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 68 of 2016, especially in the parameters of TSS, COD, BOD, and total coliform. Evaluation of the WWTP building showed that some units did not meet the expected design criteria, such as the initial and final reservoirs that had too large a volume and inappropriate residence times. Suggestions for improvement include installation of a mechanical mixer system